Does the wall thickness of the left atrial appendage and its isthmus depend on their macroscopic characteristics? - A. A. Gaponov; E. G. Dmitrieva; Ya. S. Malov; A. A. Iakimov (Сибирский научный медицинский журнал, 2023)
Knowledge in interrelations between gross anatomy of the left atrial appendage (LAA) and thickness of the walls of LAA and periauricular area enables decreasing operational risks in LAA ostium occluding and «Cox-Maze» surgery for atrial fibrillation. The aim of the study was to identify significant interrelations between the macroscopic characteristics of the LAA (size, shape, number of lobes) and the parameters of the wall thickness of the LAA and its isthmus. Material and methods. The study includes 50 heart specimens of patients died from non-cardiac diseases. We examined 60 anatomical sections from 30 hearts by means Olympus SZX2-ZB10 microscope, and histological slices from 20 hearts. Results. The layers of the LAA wall were thinner than those in the isthmus. The thickness of LAA walls did not show direct correlation with the external dimensions of LAA. We found inverse correlation (Rs = – 0.4, p < 0,05) between the thickness of the myocardium, endocardium and some external sizes of LAA. The wall thickness of «chicken wing», «cauliflower» and «arrowhead» was the same. The wall of single-lobe LAA was thinner than that of two-lobed LAA (p = 0.036). The LAA isthmus wall was thinner (p = 0.03) in hearts with «cauliflower» LAA compared to hearts with LAA resembled a «chicken wing». Differences in wall thickness in LAA of various shapes were due to the degree of subepicardial fatty tissue development. Intracardiac operations should be done with the utmost care in patients with «cauliflower» LAA and single-lobe LAA to avoid damage of the LAA and periauricular area. Conclusions. The research found clinically significant interrelations between the LAA wall thickness and the number of its lobes as well as between the LAA isthmus wall thickness and LAA shape variants.